Scarcity mindset among schoolteachers: how resource scarcity negatively impacts teachers’ cognition and behaviors - Denti, Leif; Sturén, Erik; Johansson, Lars-Olof (Frontiers in Psychology, 2024)
A recent line of research investigates the negative cognitive effects – known as the scarcity mindset – that arise when people face a lack of resources. We expand on this research and show that these cognitive effects are present among Swedish schoolteachers facing a scarcity of time and social resources at work. From an initial interview study we developed novel survey scales to measure teachers’ subjective assessments of available resources and the extent of their scarcity mindset. We then related resource scarcity of time and social resources to the scarcity mindset using structural equation modeling (SEM) analysis in a survey study with a sample of Swedish schoolteachers. This research provides valuable insights for addressing resource constrained work environments in schools and contributes to the broader psychological research on cognitive effects resulting from resource scarcity.